2015
DOI: 10.1111/eos.12226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metabolic syndrome on masseter muscle of male Wistar rats

Abstract: The aim of this study was to investigate the association between metabolic syndrome (MetS) and the metabolic indicators of masticatory muscles in an animal model. A total of 16 male Wistar rats were used. To induce MetS, 10 rats were fed with standard rat chow and 32% sucrose solution ad libitum for 16 wk. Six rats fed with standard rat chow and water ad libitum formed the control group. All rats were killed at week 16, and the right superficial masseter muscles were harvested. Metabolic indicators of masticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Increased GR activity also indicated that GSH metabolism was affected from MetS. In our previous study, activities of SOD, CAT, GPx, GR were all significantly decreased in the masseter muscles of rats with MetS (16). These results demonstrated that the effects of MetS on different tissues varied depending on the metabolic functions of the tissues.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…Increased GR activity also indicated that GSH metabolism was affected from MetS. In our previous study, activities of SOD, CAT, GPx, GR were all significantly decreased in the masseter muscles of rats with MetS (16). These results demonstrated that the effects of MetS on different tissues varied depending on the metabolic functions of the tissues.…”
Section: Resultsmentioning
confidence: 59%
“…This may result in mitochondrial dysfunction with time and finally, cause MetS. In our previous study, we found that Cu level increased in the masseter muscle of rats with MetS while Fe and Mn levels were like those of controls (16). In the literature, increased Fe and Cu levels and decreased Mn and Zn levels were reported in liver of rats fed a high carbohydratehigh fat diet for up to 16 weeks (38).…”
Section: Nestorov Et Al Reported An Increased Expression Ofmentioning
confidence: 79%
See 2 more Smart Citations
“…Previously, it has been reported that short‐term dietary fructose induces oxidative stress via suppressing antioxidant enzymes (Cigliano et al., 2018). It was determined that SOD, GPx, and catalase levels were decreased in masseter muscles of Wistar rats given 32% sucrose in drinking water for 16 weeks (Tukel et al., 2015). Cavarape et al.…”
Section: Discussionmentioning
confidence: 99%